LIFE CYCLE MANAGEMENT DESIGN FOR THE SUPPLY CHAIN LOGISTICS ECOSYSTEM - LESNIKOV, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Contemporary globalization processes and rapid technological transformations have significantly undermined the efficiency of linear approaches to supply chain management. The increasing complexity of economic relationships, the intensification of competitive-cooperative interactions among business entities, and the advancement of digital technologies have catalyzed the emergence of ecosystem-based concepts in logistics management. These approaches aim to generate synergistic effects through collaboration and enhance operational resilience by fostering adaptability. This article aims to develop theoretical, methodological, and practical foundations for organizing adaptive life cycle management of the supply chain logistics ecosystem under growing environmental uncertainty and volatility. The research methodology integrates organizational ecology and systems engineering theories with object-oriented modeling. A formal predicate logic apparatus describes interactions among ecosystem business objects and models their states and transitions. The study proposes a conceptual model of a logistics ecosystem comprising three architectural levels: constructive (physical identity of business objects), functional (behavioral dynamics through state transitions), and managerial (oversight and coordination of processes). A logistics ecosystem life cycle model is introduced, aligning development stages with specific operational methods. The advantages of the ecosystem approach are substantiated, including the virtualization of interactions, institutionalization of trust, dynamic pricing mechanisms, and optimal order allocation. The scientific novelty lies in presenting the supply chain as an ecosystem formed by interacting business objects, formalizing their states and transitions via predicate logic, and modeling the ecosystem’s life cycle using the concept of model time from systems engineering. This representation forms the basis for enhancing the adaptability and resilience of supply chains and for designing digital platforms to manage logistics ecosystems through implementing Industry 4.0 technologies.